Knowledge-based Risk Management: A Systematic Literature Review - Neto, Ademar; Perkusich, Mirko; Dantas, Emanuel; Ramos, Felipe; Costa, Alexandre; Almeida, Hyggo; Perkusich, Angelo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Knowledge management can enhance project risk management effectiveness by supporting the reuse of risk-related knowledge, supporting decision-making. This paper explores this hypothesis by identifying and analyzing the state of the art of studies addressing knowledge-based risk management, seeking solutions that present the process of reusing risk-related knowledge. To this end, we conducted a Systematic Literature Review, applying a hybrid approach that combined a search on the Scopus database with snowballing (backward and forward). We applied Thematic Analysis to the primary studies to identify the main attributes of existing knowledge-based risk management solutions and their relationships. In total, we evaluated 1363 papers and identified 7 reported solutions on the topic. The resulting thematic network comprises one higher-level theme: the Risk Repository; and five middle-level: Knowledge capture, Knowledge codification, Embed Knowledge, Shared Knowledge, and Knowledge application. An implication for research is the need to propose tools and algorithms to support the reuse of knowledge for project risk management. Also, provide practical assessments of the feasibility and utility of these solutions. Furthermore, the Thematic Network can be generalized and used as a basis for researchers who intend to explore knowledge-based risk management. For practitioners, the Thematic Network can help them understand reusing risk knowledge and use the resources already existing in the company to improve organizational learning in risk management.